Konsumsi Junk Food dan Asupan Serat terhadap Status Gizi Remajadi SMP Negeri 9 Palu - Ayu Sri Wahyuni; Sri Rezeki Pettalolo; Ni Ketut Kariani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Adolescence is a crucial stage of human development, during which adequate and balanced nutrition plays an important role in supporting growth and maintaining long-term health. At this age, eating habits begin to form, yet many adolescents tend to choose fast food, which generally has low nutritional value. Such foods are typically high in fat, sugar, and salt, but low in fiber from fruits and vegetables, potentially affecting their nutritional status. This study aims to examine the relationship between the frequency of Junk Food consumption and fiber intake with the nutritional status of students at SMP Negeri 9 Palu. This research employed an analytical quantitative approach using a cross-sectional design, involving a population of 97 students. Data were collected through the SQ-FFQ questionnaire to assess Junk Food consumption, 3×24-hour dietary recalls to measure fiber intake, and anthropometric measurements to determine nutritional status. Data analysis was conducted using the chi-square test. The results indicated a significant relationship between Junk Food consumption and nutritional status (p < 0.05). In contrast, fiber intake showed no meaningful association (p > 0.05), possibly because most respondents had similarly low fiber intake, resulting in insufficient variation to influence nutritional status. Other factors such as total energy intake, physical activity, and sleep patterns may also contribute to adolescents’ nutritional conditions. These findings highlight the importance of nutrition education in schools and the role of parents in monitoring adolescents’ eating habits. Further research with a larger sample size and more detailed dietary assessment methods is recommended to obtain more comprehensive results.